The monk on the roof: the story of an Ethiopian manuscript found in Jerusalem (1904) - Ancel, Stéphane (Open Jerusalem Ser., 2021)
Centred on the changing fortunes of the Ethiopian Christian community in Jerusalem around 1900, this book takes the reader to the heart of the political, diplomatic and religious affairs that exercised the city's multinational population.